Instructional Design for Teaching Speaking Skill to the Eight Grade Students of SMP Muhammadiyah 4 Surkarta in 2015/2016 Academic year: A Naturalistic Study - Astuti, Nanik Ayu, Prof. Dr. Endang Fauziati, M. Hum, Siti Fatimah, S. Pd M. Hum (2016)
ABSTRACT This research is aimed at observing the instructional design on teaching speaking skill at eight grade of SMP Muhammadiyah 4 Surakarta in 2015/2016 academic year. The objective of the study is to describe instructional design in teaching learning process of speaking skill at SMP Muhammadiyah 4 Surakarta. In this research, there are eight components of instructional design in teaching speaking skill that the researcher analyze, namely: (1) Learning Objective. (2) Classroom Procedure. (3) Classroom Technique. (4) Instructional Material. (5) Media (6) Teacher Role. (7) Student Role, (8) Assessment. The type of the study is descriptive qualitative research especially naturalistic approach. In this research, the data derived from event, informant, and field note. There are three techniques of collecting data, namely: observation, interview and documentation. Techniques for analyzing data are reduction of the data, display of data, and conclusion. The results of the study are: (1) There are general learning objective and specific learning objective in teaching speaking skill. (2) Classroom procedure used Exploration, Elaboration, Confirmation. (3) Classroom techniques used in teaching speaking skill are question and answer, discussion, role-play, giving feedback and summarizing. (4). The kind of instructional materials printed and unprinted material that compare both print and non-print source as access material and material on the internet. The role of instructional material are as a resource for presentation, a source of activities for learner practice and communicative interaction (5) Media used by the teacher in teaching speaking skill are picture and LCD. (6) The English teacher roles are as facilitator, organizer, motivator, participant, observer. (7)) The learner roles are as the leaner is monitor and evaluator of his or her own progress, the learner is a member of a group and learning by interacting with others, the leaner learns from the teacher, from Other Students and other Teaching Sources. (8) Assessment for teaching speaking is that the teacher used is answer and question. Keywords: Instructional Design, Teaching learning Process, Speaking Skill.